A horizon scan of biological conservation issues for 2026 - William J. Sutherland; Stuart H.M. Butchart; Stewart J. Clarke; Nigel R. Doar; Helen Doran; Imogen C. Douglas; Daniel J. Field; Erica Fleishman; Kevin J. Gaston; James E. Herbert-Read; Alice C. Hughes; Hermanni Kaartokallio; et al. (Trends in Ecology & Evolution, 2026)

Acoustic Monitoring Enables Multi‐Taxa Conservation Assessment and Prioritisation Over Large Scales and for Rare and Cryptic Species - Adham Ashton‐Butt; Stuart E. Newson; Jeffrey W. Doser; Simon Gillings; Tatiana Kornienko; Viktar Fenchuk; James W. Pearce‐Higgins; Chris Scott; Philip W. Atkinson (Global Ecology and Biogeography, 2025)
Aim To combat the global biodiversity crisis, robust and scalable data are needed to target, monitor and evaluate conservation efforts, particularly in data‐poor regions and for cryptic taxa. Passive acoustic monitoring (PAM) has the potential to provide solutions, but real‐world examples are still rare. We demonstrate how PAM data can be used to rapidly and effectively map distributions of multiple taxa over large scales, in data‐poor regions. We show how these data can be used to assess the importance of existing protected areas and prioritise future conservation efforts, including for rare and cryptic species often neglected in such assessments. Location Global with a case study from Polesia, Eastern Europe. Time Period Present. Major Taxa Studied Bats, Birds, Small mammals and Bush crickets. Methods Using machine‐learning and manual verification, we identified bats, nocturnally active birds, small mammals and bush crickets from over 34,000 monitoring hours at 506 sites in the Polesia region of Belarus and Ukraine. Using multi‐species generalised mixed models in a Bayesian framework, we then predicted occupancy and acoustic activity for these species and their associations with protected areas, over a 151,000 km 2 project area. We identified areas of high conservation priority as measured by species richness and/or importance for globally or regionally threatened species. Main Conclusions Our approach provides a roadmap for collecting and processing large‐scale, multi‐taxa biodiversity data using passive acoustic monitoring. In our case study region, we show that although existing protected areas contain a relatively large proportion of high conservation priority areas, there are significant gaps in the protected area network. We also show low surrogacy of areas of high conservation priority between taxa at fine scales, but did at larger scales, showing the importance of multi‐taxa monitoring to prioritise protected areas that conserve a wide variety of species.

Normal fault localization controls during syn- and post-orogenic extension affecting thin-skinned architecture - Michal Nemčok; Andreas Henk; Charles J. Stuart; Dian Vangelov; R. Eric Higgins; Chelsea Welker; Lucia Ledvényiová (Journal of Structural Geology, 2024)

A horizon scan of global biological conservation issues for 2024 - William J. Sutherland; Craig Bennett; Peter N.M. Brotherton; Stuart H.M. Butchart; Holly M. Butterworth; Stewart J. Clarke; Nafeesa Esmail; Erica Fleishman; Kevin J. Gaston; James E. Herbert-Read; Alice C. Hughes; Jennifer James; et al. (Trends in Ecology & Evolution, 2024)

Degradation and lifetime prediction of plastics in subsea and offshore infrastructures - Ibukun Oluwoye; Laura L. Machuca; Stuart Higgins; Sangwon Suh; Tamara S. Galloway; Peter Halley; Shuhei Tanaka; Mariano Iannuzzi (Science of The Total Environment, 2023)

Threshold values for the protection of marine ecosystems from NORM in subsea oil and gas infrastructure - Darren J. Koppel; Tom Cresswell; Amy MacIntosh; Rebecca von Hellfeld; Astley Hastings; Stuart Higgins (Journal of Environmental Radioactivity, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Setting priorities for climate change adaptation of Critical Sites in the Africa‐Eurasian waterbird flyways - Frank T. Breiner; Mira Anand; Stuart H. M. Butchart; Martina Flörke; Etienne Fluet‐Chouinard; Antoine Guisan; Lammert Hilarides; Victoria R. Jones; Mikhail Kalyakin; Bernhard Lehner; Merijn van Leeuwen; James W. Pearce‐Higgins; et al. (Global Change Biology, 2022)
Despite their importance for biodiversity and ecosystem services, wetlands are among the most threatened ecosystems globally. The conservation of many migratory waterbirds depends on the conservation of a network of key sites along their flyways. However, the suitability of these sites is changing under climate change, and it is important that management of individual sites in the network adapts to these changes. Using bioclimatic models that also account for changes in inundation, we found that projected climate change will reduce habitat suitability for waterbirds at 57.5% of existing Critical Sites within Africa‐Eurasia, varying from 20.1% in Eastern Europe to 87.0% in Africa. African and Middle East sites are particularly threatened, comprising 71 of the 100 most vulnerable sites. By highlighting priority sites for conservation and classifying Critical Sites into Climate Change Adaptation Strategy (CCAS) classes, our results can be used to support the climate change adaptation of both individual sites and the entire site network.

Mechanisms underpinning climatic impacts on natural populations: altered species interactions are more important than direct effects - Nancy Ockendon; David J. Baker; Jamie A. Carr; Elizabeth C. White; Rosamunde E. A. Almond; Tatsuya Amano; Esther Bertram; Richard B. Bradbury; Cassie Bradley; Stuart H. M. Butchart; Nathalie Doswald; Wendy Foden; et al. (Global Change Biology, 2014)
Shifts in species' distribution and abundance in response to climate change have been well documented, but the underpinning processes are still poorly understood. We present the results of a systematic literature review and meta‐analysis investigating the frequency and importance of different mechanisms by which climate has impacted natural populations. Most studies were from temperate latitudes of North America and Europe; almost half investigated bird populations. We found significantly greater support for indirect, biotic mechanisms than direct, abiotic mechanisms as mediators of the impact of climate on populations. In addition, biotic effects tended to have greater support than abiotic factors in studies of species from higher trophic levels. For primary consumers, the impact of climate was equally mediated by biotic and abiotic mechanisms, whereas for higher level consumers the mechanisms were most frequently biotic, such as predation or food availability. Biotic mechanisms were more frequently supported in studies that reported a directional trend in climate than in studies with no such climatic change, although sample sizes for this comparison were small. We call for more mechanistic studies of climate change impacts on populations, particularly in tropical systems.